PALEOGENE PALYNOLOGY OF THE CENTRAL SUMATERA BASIN - Eko Budi Lelono; Christina Ani Setyaningsih; L Nugrahaningsih (Testing Center for Oil and Gas LEMIGAS, 2014)
Unlike rich pollen assemblage of other Paleogene sediments in western Indonesia (as seen in NanggulanFormation of Central Java, Tanjung Formation of South Kalimantan and Malawa Formation of SouthSulawesi), pollen assemblage of Paleogene sediments in the Central Sumatera Basin is considerablylow. Referring to the occurrence of Oligocene spore Cicatricosisporites dorogensis supported by pollenPalmaepollenites kutchensis and Meyeripollis naharkotensis, it is inferred that the studied sediment isassigned to Oligocene age. This is strengthened by the disappearance of many key Indian affi nities whicharrived in the Sundaland during Eocene. Palynologically, this study separates the Brown Shale from theUpper Red Bed. The Brown Shale is dominated by fresh water pollen without brackish element suggestingnon-marine environment. This sequence might have been formed in syn-rift setting. Surprisingly, lacustrineindicators of fresh water algae Botriococcus and Pediastrum (as found in the lacustrine sediment of TalangAkar Formation of Sunda-Asri Basin) are absent. Mean while, the Upper Red Bed is marked by signifi cantoccurrence of brackish palynomorphs suggesting the infl uence of marine environment during post-rift period.This condition proves the existence of the transgressive phase where sedimentation started in freshwaterenvironment during the Brown Shale deposition which gradually shifted into transition (shallow marine)environment during the Upper Red Bed sedimentation.